Effects of A1/A2‐Sites Occupancy upon Ferroelectric Transition in (SrxBa1−x)Nb2O6 Tungsten Bronze Ceramics. Issue 2 (7th December 2013) - Huang, C. J.; Li, K.; Liu, X. Q.; Zhu, X. L.; Chen, X. M.
Abstract : The dielectric and ferroelectric characteristics of (Sr x Ba1− x )Nb2 O6 unfilled tungsten bronze ceramics have been investigated together with the structure. The dielectric and ferroelectric characteristics of the present ceramics vary significantly with x, and the A1/A2‐sites occupancy has been determined as the primary parameter governing this variation tendency. Ba ions tend to occupy A2‐sites, Sr ions tend to occupy A1‐sites, and one A1‐site is empty. When the ratio of Sr/Ba is close to 1:4 (where four A2‐sites are just occupied by Ba ions, and one A1‐site is occupied by Sr ion while another A1‐site is empty), the normal ferroelectric transition is observed with one anomaly in the tanδ– T curve ( x  = 0.25). When the ratio of Sr/Ba is far away from 1:4, the typical relaxor behavior is indicated together with three anomalies in the tanδ– T curve ( x  = 0.75). The incommensurate oxygen octahedral tilting and A‐site random distribution are considered to be the structure origins for the relaxor ferroelectricity and low temperature dielectric relaxations.